(untitled) (Global Journal of Human-Social Science, 2016)
Self-esteem is one of the most pertinent notions that has enjoyed a long period of interest. Researches findings on self-esteem posit that a healthy level of self-esteem usually results in positive outcomes and reflects on behaviours, performances and even personal handwriting. Thus, the current paper highlights the eminence of self-esteem for foreign/second language teachers. It also aims at, not only measuring, but examining the connection between sundry self-esteem’ elements. First, in order to demonstrate the significance of self-esteem’ implication in teaching, a general definition to the teaching process is necessary. Second, we will essay to explain the main methodology and the primary tools selected. Finally, on the data analysis and interpretation, we will endeavour to suggest some techniques that can upsurge selfesteem.